Women in Western political thought - Okin, Susan Moller (Princeton University Press, 2013)
In this pathbreaking study of the works of Plato, Aristotle, Rousseau, and Mill, Susan Moller Okin turns to the tradition of political philosophy that pervades Western culture and its institutions to understand why the gap between formal and real gender equality persists. Our philosophical heritage, Okin argues, largely rests on the assumption of the natural inequality of the sexes. Women cannot be included as equals within political theory unless its deep-rooted assumptions about the traditional family, its sex roles, and its relation to the wider world of political society are challenged.
Keywords: amériques; approches et analyses; cours; discipline; fem1000; inégalités; philosophie politique; premier cycle; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; théories féministes; états-unis

Justice, genre et famille - Okin, Susan Moller (Champs (Flammarion (Firme)), 2008)
Considérant que "le mariage et la famille, tels qu'ils sont pratiqués dans notre société, sont des institutions injustes", Susan Moller Okin refuse toutefois de se contenter de montrer en quoi ils favorisent l'inégalité entre les hommes et les femmes. Car il faut aussi et surtout, à ses yeux, défendre la nécessité d'étendre la réflexion sur la justice à la sphère familiale. Sa question primordiale est de savoir dans quelle mesure il est possible de faire co-exister la justice et le genre.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; care; cours; discipline; europe; famille; france; mariage; phi2030; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques